Analýza chování radiového systému s adaptivním frekvenčním skákáním v podmínkách intenzivního rušení - Pust, Radim (International Society for Science and Engineering, o.s., 2008)
The technique of frequency hopping has been well known for many years. Today this technique is used in stations where a higher interference immunity and secure connection are requested. The goal of this article is to describe the mathematical models for behaviour systems with frequency hopping and adaptive frequency hopping in conditions of intensive interference and to compare both above techniques.

Technika frekvenčního skákání je v radiové technice již známa řadu let, avšak v dnešní době nachází uplatnění ve stanicích, kde požadujeme vyšší odolnost vůči rušení případně utajení přenosu. Cílem tohoto článku je popsat matematické modely chování systémů s technikou frekvenčního skákání a adaptivního frekvenčního skákání v podmínkách intenzivního rušení a navzájem obě uvedené techniky porovnat.
Behaviour analysis of radiocommunication system with adaptive frequency hopping in conditions of intensive interference.
Keywords: FH; AFH; frekvenčním skákání; adaptivní frekvenčním skákání; FH; AFH; Frequency Hopping; Adaptive Frequency Hopping